Theoretical Study of the Effect of Instrument Parameters on the Flow Field of Air-Flow Impacting Based Mechanochemical Synthesis. (24th May 2018) - Tao, Yang; Lin, Jun; Zhang, Zhao; Guo, Qiuting; Zuo, Jin; Lu, Bo
Abstract : The air-flow impacting based mechanochemical synthesis is an alternative strategy to traditional mechanochemical preparations, which has many advantages in terms of reaction temperature, preparation speed, and cleanness. Herein, we theoretically study the effect of instrument parameters, including the axial position of physical target, the diameter difference between nozzle throat and suction pipe, and divergence angles of uniform speed region, on the flow field of the air-flow impacting based mechanochemical synthesis. The optimized parameters have been obtained. Under the optimal conditions, a stable and high-speed air flow is obtained, in which the speed can achieve a Mach number of approximately 2.6. The high-speed air flow is able to easily carry the reacting substances to arrive at the physical target, triggering a chemical reaction. These findings undoubtedly provide a key guideline for further development and application of the air-flow impacting based mechanochemical synthesis.